2009
DOI: 10.1177/1088767909352829
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Culture, and Lethality: An Integrated Model Approach to American Indian Suicide and Homicide

Abstract: Investigations of lethal violence in the United States have primarily focused on Whites and/or African Americans, generally ignoring American Indians. Interestingly, statistics indicate that homicide and suicide rates among American Indians are often higher than other racial/ethnic groups within the United States. In an attempt to understand these lethal violence patterns, the current study utilizes the integrated model of suicide and homicide to investigate the structural and cultural factors that contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…For instance, a Canadian study that used interrupted time-series analyses concluded that a new law on firearms restriction may have been responsible for a reduction in suicide rates (Carrington & Moyer, 1994). There is evidence that the means by which people choose to die differ across race and that certain communities of color may have preferred methods of suicide (Lainer, 2010;Lester, 1994). There is evidence that the means by which people choose to die differ across race and that certain communities of color may have preferred methods of suicide (Lainer, 2010;Lester, 1994).…”
Section: Principle 9: Incorporate Environment-centered Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a Canadian study that used interrupted time-series analyses concluded that a new law on firearms restriction may have been responsible for a reduction in suicide rates (Carrington & Moyer, 1994). There is evidence that the means by which people choose to die differ across race and that certain communities of color may have preferred methods of suicide (Lainer, 2010;Lester, 1994). There is evidence that the means by which people choose to die differ across race and that certain communities of color may have preferred methods of suicide (Lainer, 2010;Lester, 1994).…”
Section: Principle 9: Incorporate Environment-centered Interventionsmentioning
confidence: 99%
“…Means restriction is effective because many people have a preference for a suicide method; hence, people with restricted access to a suicide means may not necessarily turn to alternative means of suicide (Daigle, 2005). There is evidence that the means by which people choose to die differ across race and that certain communities of color may have preferred methods of suicide (Lainer, 2010;Lester, 1994). Stack and Wasserman (2005) found that Black Americans were more than 2 times as likely as White Americans to use violent means of suicide (e.g., hanging and firearms).…”
Section: The Counseling Psychologist 42(1)mentioning
confidence: 99%
“…In an examination of a sample of 30 adult American Indian homicide offenders, Bachman (1991) reported that the majority of offenders in the sample killed with a knife (40%) and as a result of an interpersonal conflict (67%). The proliferation of knife and conflict-related homicides among American Indians may be attributed to frustration that stems from the structural disadvantage faced by many American Indians, as well as the strong culture of honor in Native American communities (Bachman, 1991; Lanier, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The macrosocial research on American Indian violent crime that does exist has focused exclusively on American Indian homicide victimization (Bachman, 1991a; Lanier, 2010; Lanier & Huff-Corzine, 2006). As will be discussed in detail, American Indian homicide victimization is a weak proxy for American Indian violent offending because (a) American Indians are more likely to be victimized by individuals of another race (Greenfeld & Smith, 1999; Perry, 2004), and (b) the race of American Indians is often misclassified in coroners’ reports (Arias, Schauman, Eschbach, Sorlie, & Backlund, 2008).…”
mentioning
confidence: 99%
“… 3. Lanier’s (2010) county-level analysis of violence among American Indians was not included because her dependent measures were not pure measures of violence. Her first measure combined suicide and homicide victimization, and her second measure was a ratio of homicide victimization to suicide. …”
mentioning
confidence: 99%